Effect of warfare waste on soil: a case study of Gallipoli Peninsula (Turkey). (31st January 2005) - Baba, Alper; Deniz, Ozan
Gallipoli is a small town on the European side of the Dardanelles Strait, in Turkey. More than 450, 000 soldiers gave their lives on the Gallipoli Peninsula (Gallipoli Campaign) over a nine-month period during World War I. In that war, many naval and landing bombs were exploded. The ingredients of these bombs may cause heavy metal contamination in soils. An environmental geochemical investigation has been carried out around Gallipoli Peninsula in order to determine the extent of chemical pollution in the soil. The preliminary data reveal that soils in the area are, in general, not contaminated. The concentrations of many heavy metals, such as arsenic (As), cadmium (Cd), copper (Cu), chromium (Cr), cobalt (Co), manganese (Mn), nickel (Ni), lead (Pb), strontium (Sr), vanadium (V) and zinc (Zn) are in the range of those of average agricultural soils. These low concentrations are explained by the good leaching characteristics of Oligocene–Miocene rocks, Pleistocene terrace material, alluvium sandy-silty soils, and surface run-off.